A sensor-less contact torque estimation and haptic feedback method in minimally invasive surgery. (1st November 2019) - Bai, Dongming; Chen, Bai; Qi, Fei; Ju, Feng; Wang, Yaoyao
To satisfy the needs of surgeons for judging the contact state of the catheter robot and modify the operation accordingly, a novel contact torque estimation and haptic feedback method is proposed in this article. Using the vibrotactile feedback, the proposed method reminds the surgeon which bending unit of the robot contacts with human tissue and guides him to realize the disengagement. Based on a novel simplification of the driving force of the robot, a quasi-statics model is established to estimate the contact torque. Simulations are conducted based on Finite Element Method (FEM) to verify the accuracy of the quasi-statics model and the estimation method. A robot system composed of a catheter robot, a PC, a master-operator, and a wearable vibration glove is assembled according to this method. To verify the feasibility of this method, a contact torque estimation experiment and a vibrotactile feedback experiment are conducted in this article. The results show that this method is accurate and effective.